2017
DOI: 10.1536/ihj.16-292
|View full text |Cite
|
Sign up to set email alerts
|

SYNTAX Score-II Predicts Long-Term Mortality in Patients Who Underwent Left Main Percutaneous Coronary Intervention Treated With Second-Generation Drug-Eluting Stents

Abstract: SummaryThe aim of this study was to evaluate the capacity of the SYNTAX Score-II (SS-II) to predict long-term mortality in patients undergoing left main percutaneous coronary intervention (LM-PCI) treated with second-generation drug-eluting stents (DES).Data from 487 consecutive patients with de novo left main coronary artery disease undergoing PCI were retrospectively studied. The patients were divided into tertiles according to the SS-II: low SS-II tertile (SS-II ≤ 22), intermediate SS-II tertile (SS-II of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…SYNTAX score (SS) I and II are recent scores which are used for choosing the treatment modality in patients with multivessel disease. During the last decade, several studies showed a close association between these scores and cardiovascular outcomes [5-8] . The aim of our study is to determine the association between SS I-II and significant CAS in patients with multivessel disease undergoing CABG.…”
Section: Introductionmentioning
confidence: 99%
“…SYNTAX score (SS) I and II are recent scores which are used for choosing the treatment modality in patients with multivessel disease. During the last decade, several studies showed a close association between these scores and cardiovascular outcomes [5-8] . The aim of our study is to determine the association between SS I-II and significant CAS in patients with multivessel disease undergoing CABG.…”
Section: Introductionmentioning
confidence: 99%
“…Brkovic et al found that SYNTAX score was superior to GRACE risk score, TIMI blood flow grading score, PAMI score and ZWOLLE score in predicting MACE events and cardiovascular mortality [15]. He's and other studies showed that in the use of the second generation of drug-eluting stents (DES) for the treatment of left main lesion patients, SYNTAX II score is an independent predictor of long-term mortality and has better predictive value than SYNTAX score [16]. For our study, we focused on the prognostic value of different SYNTAX scores in universal ACS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Brkovic et al found that SYNTAX score was superior to GRACE risk score, TIMI blood flow grading score, PAMI score and ZWOLLE score in predicting MACE events and cardiovascular mortality [15]. He`s and other studies showed that in the use of the second generation of drugeluting stents (DES) for the treatment of left main lesion patients, SYNTAX II score is an independent predictor of long-term mortality and has better predictive value than SYNTAX score [16]. For our study, we focused on the prognostic value of different SYNTAX scores in universal ACS patients.…”
Section: Discussionmentioning
confidence: 99%